2023
DOI: 10.3390/diagnostics13132175
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines in Breast Cancer: Challenges and Breakthroughs

Gul Naz Fatima,
Hera Fatma,
Shailendra K. Saraf

Abstract: Breast cancer is a problem for women’s health globally. Early detection techniques come in a variety of forms ranging from local to systemic and from non-invasive to invasive. The treatment of cancer has always been challenging despite the availability of a wide range of therapeutics. This is either due to the variable behaviour and heterogeneity of the proliferating cells and/or the individual’s response towards the treatment applied. However, advancements in cancer biology and scientific technology have chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 209 publications
(259 reference statements)
0
3
0
Order By: Relevance
“…Seeking to produce more precise and repeatable outcomes, AI algorithms have been created to analyze TILs in light of the increased adoption of digital pathology. The degree of lymphocytic infiltrate in HER2 breast carcinoma was consequently detected and graded in one study using WSIs 63 . The outcomes demonstrated that the architectural set of characteristics effectively differentiated samples with high and low lymphocytic infiltrate the amount with a precision of classification greater than ninety percent 64 .…”
Section: Ai In Breast Pathologymentioning
confidence: 99%
“…Seeking to produce more precise and repeatable outcomes, AI algorithms have been created to analyze TILs in light of the increased adoption of digital pathology. The degree of lymphocytic infiltrate in HER2 breast carcinoma was consequently detected and graded in one study using WSIs 63 . The outcomes demonstrated that the architectural set of characteristics effectively differentiated samples with high and low lymphocytic infiltrate the amount with a precision of classification greater than ninety percent 64 .…”
Section: Ai In Breast Pathologymentioning
confidence: 99%
“…These pathways play crucial roles in eliminating undesirable or damaged cells from the organism [ 68 , 69 , 70 ]. However, in BC, PCD becomes dysregulated, resulting in the survival and proliferation of cancer cells [ 71 , 72 , 73 ]. The process of PCD can be delineated into three stages: initiation, execution, and degradation and clearance.…”
Section: Stress Signaling and Programmed Cell Death In Bcmentioning
confidence: 99%
“…Cancer vaccines offer several advantages over traditional therapies, mainly due to increased specificity, reduced toxicity, and the long-term effect produced by immunological memory. Such vaccines can be developed as a prophylactic or therapeutic strategy, in both cases aiming at selective biodistribution to cancer cells [156]. However, factors such as the inability to identify a single gene that works in anti-tumor therapy, the lack of tumor selectivity, the short duration of therapeutic gene expression, the difficulty of transfecting the entire tumor mass, and the strong antiviral immune response generated in the host are the main limitations for the application of gene therapy [21].…”
Section: Gene Therapymentioning
confidence: 99%